The determination of fermented food awareness and the effect of the COVID-19 pandemic period on fermented food consumption in Türkiye - Ganiyusufoglu, Eda; Aytop, Yesim; Gezginc, Yekta (Progress in Nutrition, 2022)
The Covid-19 pandemic highlighted the need of creating a strong immune system while dealing with viral illnesses. Nutrition has a crucial role in immune system control. Fermented food products, which are important in nutrition, can also strengthen the immune system. In this study, we investigated the determination of the knowledge level of consumers about fermented foods as well as the effect of the COVID-19 pandemic on fermented food consumption. The data obtained from the online surveys was conducted with 600 consumers in Turkey. The surveys were repeated twice, in the first year and the second year of COVID-19. Binary logit model was used to analyse the data. According to the results, 88% of the consumers had sufficient information about COVID-19. In the first year of COVID-19, it was determined that the state of having knowledge about fermented foods was affected by gender and education, and in the second year, it was affected by gender and age. Consumers who increased their consumption of fermented foods increased their consumption of yogurt, cheese, butter, boza, and sausage in the first year of COVID-19 compared to the second year. In the second year of COVID-19, they increased their consumption of kefir, shalgam, tarhana, and pickles compared to the first year. The results will contribute to the prevention of disease by raising awareness about fermented food consumption in the COVID-19 pandemic and will provide resources for relevant stakeholders.